MICROLEAKAGE OF SAUCER-SHAPED CLASS II COMPOSITE RESIN RESTORATION: KEBOCORAN MIKRO PADA RESTORASI KLAS II RESIN KOMPOSIT BERBENTUK SAUCER - Teddy; Trimurni Abidin; Listiani Nurul Huda (Dentika: Dental Journal, 2015)
Filling techniques influence in reducing polymerization shrinkage which cause microleakage. Besides, the use of matricesalso contributes to achieve good marginal ridge. This study was aimed to examine the effect of filling techniques and theuse of matrices on microleakage of saucer-shaped Class II restorations. Mandibular premolar specimens were prepared insaucer-shaped cavity design, then they were divided into eight groups according to filling techniques (bulk orincremental), the use of matrices (circumferential or sectional), and whether load was provided or not. Specimens wereimmersed in saline for 24 hours, then thermocycled, later immersed in 2% methylene blue for 24 hours. Micro gap wasmeasured by scoring dye penetration in specimens that were sectioned mesio-distally under a stereomicroscope with 20xmagnification. Furthermore, visual analysis was performed under Scanning Electron Microscope to examine themicroleakage in details. Statistical analysis with Kruskal-Wallis test and Mann-Whitney test demonstrated that bulk andincremental filling techniques were not significantly different in microleakage (p> 0.05). This study also demonstratedthat the use of matrices was significantly different in microleakage in different filling techniques (p< 0.05), whether loadwas provided or not. This study showed that the use of matrices was important in reducing the microleakage in saucershapedClass II restorations.